Geografia da violência contra mulheres : espacialização da violência contra mulheres no município de Goiás/GO 2018 a 2023 - (:unkn) unknown (Universidade Estadual de Goiás, 2024)
The present study, conducted within the framework of the geography postgraduate program at the State University of Goiás - UEG, Cora Coralina Campus, analyzed the spatialization of violence against women in the municipality of Goiás/GO, during the period from 2018 to 2023. An interdisciplinary perspective was adopted to approach the possibility of the female body, the body as space, in its multiplicity, as a category of analysis, stemming from a feminist perspective within geography, aiming to understand the production and reproduction of space and its relationship with violence against women, examining the various spaces that are permitted and denied and where violence occurs. Bibliographic and documentary research on the topic was conducted, drawing from a post-structuralist and decolonial feminist approach, an epistemological and ontological option, intending to comprehend the geographical space related to the scale of women's bodies, the "women's body," and its relation to violence. The restriction of social or political space constitutes another cog in the maintenance of oppression and violence, as the cisheteropatriarchal system invisibilizes the struggle and achievements of women. The inequality and consequent gender-based violence perpetrated by this system lie at the root of rights violations, oppressions, and violence against women. General data at the national and state levels were presented, as displayed in the report produced by the Brazilian Forum on Public Security (FBSP, 2023). The foundational information of the main analysis, according to the proposed scope, originated from the Observatory of the State Secretariat of Public Security of Goiás - OSSPGO (GOIÁS, 2023), and as a complement and counterpoint, data obtained from the Specialized Center for Women's Care - CEAM of Goiás/GO (CEAM 2023) were used. The data reveal that the structured and structuring inequality of cisheteropatriarchy, rooted in the intersections of gender and race, produce, and reproduce violence and permeate both public and private spaces, naturalizing performative roles of victim and aggressor. The underreporting of violence, especially in rural areas, underscores the urgency of a more in-depth analysis and of political and social measures that effectively address the systemic roots of gender-based violence. In this sense, it is imperative not only to recognize violence as a structural issue but also to promote a radical change in power structures and dominant discourses that perpetuate oppression against women's bodies.
Keywords: Mulheres; Violência contra mulheres; Geografia feminista; Espaço; Women; Violence against women; Feminist geography; Space; CIENCIAS HUMANAS::GEOGRAFIA